Unlocking the Potential of MBenes in Li/Na-Ion Batteries - Zixin Li; Yao Hu; Haihui Lan; Huicong Xia (Molecules, 2025)
MBenes, an emerging family of two-dimensional transition metal boride materials, are gaining prominence in alkali metal-ion battery research owing to their distinctive stratified architecture, enhanced charge transport properties, and exceptional electrochemical durability. This analysis provides a comprehensive examination of morphological characteristics and fabrication protocols for MBenes, with particular focus on strategies for optimizing energy storage metrics through controlled adjustment of interlayer distance and tailored surface modifications. The discussion highlights these materials’ unique capability to host substantial alkali metal ions, translating to exceptional longevity during charge–discharge cycling and remarkable high-current performance in both lithium and sodium battery systems. Current obstacles to materials development are critically evaluated, encompassing precision control in nanoscale synthesis, reproducibility in large-scale production, enhancement of thermodynamic stability, and eco-friendly processing requirements. Prospective research pathways are proposed, including sustainable manufacturing innovations, atomic-level structural tailoring through computational modeling, and expansion into hybrid energy storage-conversion platforms. By integrating fundamental material science principles with practical engineering considerations, this work seeks to establish actionable frameworks for advancing MBene-based technologies toward next-generation electrochemical storage solutions with enhanced energy density and operational reliability.